2012
DOI: 10.1117/1.jbo.18.3.031108
|View full text |Cite
|
Sign up to set email alerts
|

In vivoobservation of age-related structural changes of dermal collagen in human facial skin using collagen-sensitive second harmonic generation microscope equipped with 1250-nm mode-locked Cr:Forsterite laser

Abstract: In vivo visualization of human skin aging is demonstrated using a Cr:Forsterite (Cr:F) laser-based, collagen-sensitive second harmonic generation (SHG) microscope. The deep penetration into human skin, as well as the specific sensitivity to collagen molecules, achieved by this microscope enables us to clearly visualize age-related structural changes of collagen fiber in the reticular dermis. Here we investigated intrinsic aging and/or photoaging in the male facial skin. Young subjects show dense distributions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 0 publications
0
48
0
1
Order By: Relevance
“…The consequences of those changes are atrophies and elastosis in dermis, which is exhibited by showing up of wrinkles (Uitto 2008; Yasui et al 2013). Thus the effect of anti-wrinkle peptide, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of those changes are atrophies and elastosis in dermis, which is exhibited by showing up of wrinkles (Uitto 2008; Yasui et al 2013). Thus the effect of anti-wrinkle peptide, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Both of the work [3] and the work [6] are global analysis which can't clearly indicate the location of collagen fibers. The proposed method is able to clearly segment collagen fiber region and further analyze other features including thickness and orientation diversity of collagen fibers in the future.…”
Section: Discussionmentioning
confidence: 99%
“…SHG microscopy has been applied to observe collagen fibers in the dermal layer of the human skin. Previous studies [2] indicated that during skin aging collagen production is decreased and the density of collagen fibers is reduced [3]. Besides, the disease may disorganize collagen fibers [4] and change collagen fibers structure.…”
Section: Introductionmentioning
confidence: 99%
“…5 is thought to reflect that the dermis has high moisture content and the viscous nature is retained higher by the glycosaminoglycan holding water. It is known that, with photo-aging, dermal collagen fibers decrease (Yasui et al, 2013) while glycosaminoglycan increases (Oh et al, 2011). The region pointed by dark triangles is indicated the dermal-epidermal junction.…”
Section: Discussionmentioning
confidence: 99%